Planning of an Integrated Cocoa Tourism Area Based on Spatial Analysis and Land Suitability in Petang Village, Badung Regency - A A Gde Sutrisna Wijaya Putra (Jurnal Ragam Pengabdian, 2026)
The development of agricultural commodity-based tourist areas requires technical planning that considers the physical characteristics of the area, land suitability, and integration with spatial planning policies so that it is sustainable and can be implemented. Petang Village, Badung Regency, has significant cocoa potential, but its use is not spatially directed and risks causing land function conflicts if it is not supported by planning based on technical analysis. This research aims to formulate an integrated cocoa tourism area planning based on spatial analysis and land suitability as the basis for regional development in accordance with the carrying capacity of the environment and regional spatial planning. The research method uses a technical-planning approach through spatial analysis based on geographic information systems by examining the physical parameters of the area including slope slope, altitude, morphology, soil type, rainfall, vulnerability to soil movement, and land cover, combined with the analysis of the suitability of RTRW and RDTR zoning. Data was obtained through secondary data collection, field observation, and thematic mapping of the planning area. The results of the analysis showed that most of the Petang Village area has biophysical characteristics that are suitable for the development of integrated cocoa tourism areas with medium to high levels of land suitability, especially in plantation zones with low to medium slopes, latosol soil types, and low-medium landslide susceptibility. Regional planning results in the division of functional zones that are integrated between cocoa cultivation, educational tourism, yield processing, and environmental buffer zones. The conclusion of the study shows that the spatial analysis and land suitability approach is able to produce more targeted planning of cocoa tourism areas, adaptive to the physical conditions of the region, and supports the development of areas based on sustainability and spatial planning.